A dictionary of accounting - Owen, Gary.; Law, Jonathan; Oxford University Press (Oxford ; New York : Oxford University Press, 2005)
nting, direct taxation, indirect taxation, auditing, corporate finance, etc.
This authoritative dictionary will be invaluable to a range of students and professionals in the fields of accounting and finance. Over 3500 entries provide comprehensive international coverage of financial accounting, financial reporting, management accou.
Machine derived contents note: Preface -- A-Z Dictionary.
1st edition edited by Roger Hussey.
Webibliography: p. 405-408.
Also available online via the World Wide Web, made available by Oxford Reference Online (ORO - Premium).
Keywords: Accounting -- Dictionaries; Electronic books